The Impact of a Pharmacist-Led Deprescribing Program on the Medication-Related Burden among Iraqi Hemodialysis Patients - Jasim, Ali Lateef; Falah, Mohammad Jameel; sultan, Sabah Saeedi (Iraqi Journal of Pharmaceutical Sciences, 2025)
Hemodialysis (HD) Patients have one of the most significant polypharmacy and medication burdens of any patient population. This may be partially attributed to the high number of medications prescribed to manage chronic kidney disease (CKD) and comorbid conditions. Adding to this high volume of medications, medication regimen complexity can increase based on instructions for use, frequency of dosing, and complicated dosage formulations that may be harder to use. One way to combat polypharmacy and inappropriate medication use is through medication deprescribing. The aim of this study was to assess the impact of implementing a pharmacist-led deprescribing program on the medication-related burden among HD patients. A prospective interventional, one-group, follow-up study was conducted at Wasit Center for Hemodialysis, Wasit Governorate, Iraq. Medication reconciliation followed by medication review based on the deprescribing program was done for all eligible patients, and the patients were monitored for three months for any possible complications. Two hundred and seventy patients were screened for eligibility, and only one hundred and eighteen patients were enrolled in the deprescribing program. The median age was 51.5 years (Interquartile range; IQR 39–62), 56.8% were males, and hypertension was the most common etiology for their CKD; 78% had comorbidities other than hypertension and CKD. After deprescription, there was a significant reduction in the number of medications from 6.0 (IQR 4.75–7.0) to 4.0 (IQR 3.0-5.0) (p < .001) and a reduction in the number of pills from 7.0 (6.0–9.0) to 5.0 (4.0–6.0) (p < .001). Medication-related burden assessed using the Arabic version of LMQ-3 also showed a significant reduction from 125.00 (IQR 111.75-138.0) to 114.0 (IQR 104.0-123.0) (p < .005). A pharmacist-led deprescribing program successfully reduced the number of medications and daily pills prescribed while simultaneously improving medication-related burden among hemodialysis patients.